Numerical evaluation of the flight mechanics and trajectory of a ski-jumper - Ward-Smith, A. J.; Clements, D. (Acta Applicandae Mathematicae, 1983)
The equations of motion governing the inrun and free-flight phases of a ski-jump have been set down. These equations have been used as the basis for a numerical scheme from which the in-flight trajectory and jump length have been calculated. The influence of such factors as the friction between the skis and snow, the jump technique at take-off, the angle of incidence of the airborne jumper and variations in air density have been investigated. Jump lengths consistent with those measured on the 90 m Sapporo ski-slope have been computed. Deductions are made concerning critical aspects of ski-jump technique